2015
DOI: 10.1002/jbm.b.33602
|View full text |Cite
|
Sign up to set email alerts
|

Validation of eGFP fluorescence intensity for testing in vitro cytotoxicity according to ISO 10993‐5

Abstract: ISO 10993-5 provides one of the accepted standards for testing the biotoxicity of new materials. All of the recommended test procedures rely upon the uptake or metabolism of dye by living cells. Results of direct contact tests can be potentially compromised by interaction or adsorption of the dye or its metabolic products. Therefore, the aim of the current study was to validate the use of the eGFP signal of transfected NIH-3T3 fibroblasts with the results of the MTT test in order to provide a test procedure th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 30 publications
0
13
0
Order By: Relevance
“…The results showed that both materials did not affect 3T3 cell morphology or growth. Although there are new suggested methods to assess cytotoxicity of materials (Miller et al, 2015), the cytotoxicity assay based on 3T3 cell proliferation is still considered a traditional method, and entails measuring neutral red uptake (Borenfreund et al, 1988;Borenfreund and Puerner, 1985;Repetto et al, 2008).…”
Section: Dna Damage Evaluation By Comet Assaymentioning
confidence: 99%
“…The results showed that both materials did not affect 3T3 cell morphology or growth. Although there are new suggested methods to assess cytotoxicity of materials (Miller et al, 2015), the cytotoxicity assay based on 3T3 cell proliferation is still considered a traditional method, and entails measuring neutral red uptake (Borenfreund et al, 1988;Borenfreund and Puerner, 1985;Repetto et al, 2008).…”
Section: Dna Damage Evaluation By Comet Assaymentioning
confidence: 99%
“…Viability assay was performed with human fibroblast line L929 based on the ISO 10993–5 [ 36 ]. L929 cells (ATCC, LGC Standards S.L.U., Barcelona, Spain) were seeded in 96-well culture plates (2 × 10 4 cells/well) and cultured in Dulbecco’s Modified Eagle’s Medium (DMEM) composed of NaHCO 3 (1.2 g/L), ampicillin (0.025 g/L), streptomycin (0.1 g/L), supplemented with 10% fetal bovine serum (SFB).…”
Section: Methodsmentioning
confidence: 99%
“…This test is related to direct interaction between investigated material and cell monolayer. To avoid false-negative results due to the adsorption of dye (such as MTT, XTT, WST) onto the surface of the pellets, we decided to perform an eGFP fluorescence-based assay which is a reliable and sensitive tool for testing the cytotoxicity of materials [ 69 ]. Therefore, at first, osteoblasts were transfected for stable production of enhanced GFP.…”
Section: Methodsmentioning
confidence: 99%